The startup owner's manual the step-by-step guide for building a great company - Blank, Steve (New Jersey John Wiley & Sons, Inc, 2020)
The National Science Foundation pays hundreds of startup teams each year to follow the process outlined in the book, and it's taught at Stanford, Berkeley, Columbia and more than 100 other leading universities worldwide. Why?